The scarab beetles of Santo Domingo Huehuetlan, Puebla, Mexico. Their potential as ecological indicators. - Yanes-Gómez, Gonzalo; Morón, Miguel-Angel (Instituto de Ecología, A.C., 2010)
The richness, diversity, abundance and indicator species of diversity of adults and larvae of scarab beetles from Santo Domingo Huehuetlán, Puebla, México is analyzed. The field work was done between October 2005 and September 2006, obtaining 1,020 adults specimens of 52 species included in 29 genera from three families of Scarabaeoidea, and 113 edaphicolous larvae belonging to 5 genera, 6 species and 9 morpho-species of Melolonthidae. Species accumulation curves were obtained and the abundance per site, month and capture method was estimated. Comparing the beetle communities of tropical deciduous forest (BTC) and crop lands (ZA), 34 and 36 species and 603 and 417 individuals were found in each site respectively. Shannon’s diversity index was 2.79 for ZA and 2.67 for BTC. Likewise, 82 larvae belonging to four genera were found in BTC, and 30 larvae of four genera in ZA. We select adults of 24 indicator species in BTC and 23 species in ZA, all from the subfamilies Dynastinae, Rutelinae and Scarabaeinae. The abundance of indicator species was 313 and 245 and the diversity index was 2.24 and 2.43 in ZA and BTC respectively. We conclude that the species composition of both communities is similar (49%), and the effect of farming near the forest is negligible on the scarab beetle community.